Enhanced Bandwidth Rectangular U-Slot Microstrip Antenna at 26 GHz for mmWave 5G - Amillia, Fitri; Mulyono, Muyono (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2024)
5G wireless communication technology offers faster data transmission speeds, more stable connections, and greatercapacity and bandwidth compared to previous networks. However, more advanced antenna technology must bedeveloped to overcome propagation and bandwidth problems at mmWave frequencies. The antenna is the maincomponent of the 5G wireless communication system, which uses mmWave frequencies. The purpose of this research isto design a U-slot rectangular microstrip antenna to increase bandwidth at the 26 GHz frequency. The slot-U method onthe rectangular microstrip antenna patch is used to enhance bandwidth. To realize the research method, an antennawas designed without and with a U-slot using analytical calculations, then a simulation was carried out by comparingthe microstrip antenna designs with and without a U-slot, after which an evaluation of the performance of the antennaparameters was carried out. The simulation results show that the U-slot rectangular microstrip antenna design showsan increase in bandwidth, gain, and directivity of 119.14%, 42.66%, and 18.79%, respectively, compared to therectangular microstrip antenna without slots. The U-slot rectangular microstrip antenna design has succeeded inincreasing bandwidth and other performance parameters, so it can be recommended for mmWave 5G applications.